2019
DOI: 10.1016/j.ymthe.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeting a Pre-existing Anti-transgene T Cell Response for Effective Gene Therapy of MPS-I in the Mouse Model of the Disease

Abstract: Mucopolysaccharidosis type I (MPS-I) is a severe genetic disease caused by a deficiency of the alpha-L-iduronidase (IDUA) enzyme. Ex vivo hematopoietic stem cell (HSC) gene therapy is a promising therapeutic approach for MPS-I, as demonstrated by preclinical studies performed in naive MPS-I mice. However, after enzyme replacement therapy (ERT), several MPS-I patients develop anti-IDUA immunity that may jeopardize ex vivo gene therapy efficacy. Here we treat MPS-I mice with an artificial immunization protocol t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…A potential concern with the older in life approach is the busulfan conditioning cell ablation regimen used as adults (irradiation was used for the neonate transplants as analogous conditioning). We did not observe any overt side effects with the busulfan conditioning, and as it is being used clinically for other disorders, our data demonstrate strong evidence for the use of this therapy to treat AS ( 52 ).…”
Section: Discussionsupporting
confidence: 59%
“…A potential concern with the older in life approach is the busulfan conditioning cell ablation regimen used as adults (irradiation was used for the neonate transplants as analogous conditioning). We did not observe any overt side effects with the busulfan conditioning, and as it is being used clinically for other disorders, our data demonstrate strong evidence for the use of this therapy to treat AS ( 52 ).…”
Section: Discussionsupporting
confidence: 59%
“…A more complex immune response to ERT, including both humoral and T cells response, cannot be ruled out, as recently suggested by Squeri et al, who studied MPS I mice and found the activation of an innate response inducing anti-IDUA CD8+ T cells in concomitance with ERT [216].…”
Section: Immunogenicitymentioning
confidence: 90%
“… 134 , 135 Moreover, a recent study has shown that enzyme replacement therapy for treatment of lysosomal storage disorders (LSDs) may induce CD8 + T cells that can target LV HSC gene therapy. 136 , 137 Therefore, ex vivo gene therapy for LSDs in patients with prior protein therapy may require adjunct immunotherapy. Others are using ex vivo HSC gene transfer with LV vectors to target transgene expression to megakaryocytes for protein delivery via platelets.…”
Section: Main Textmentioning
confidence: 99%